EVALUASI KEBIJAKAN PENGAWASAN PENGGUNAAN PESTISIDA DI KABUPATEN SIGI - Hilda, Andi (Katalogis, 2015)
The local government issued a policy on the establishment of investigation committees who are in charge of supervising the pesticide provision, distribution, use of fertilizers and pesticides in a coordinated way between the center and the regions, between relevant agencies in field of fertilizers and pesticides in the use and distribution of pesticides. This study aims at finding out the description of the evaluation of pesticide control policies in District Sigi. This type of research used is qualitative research with descriptive research method. The informants are Pesticides Control Commission and Chairman of Farmers Group in District Sigi consisting of 5 people. The research result indicates that of the six indicators of policy implementation evaluation, there are two indicators which become problem and should be considered in the implementation of policy implementation namely effectiveness that is considered not running effectively based on a comparison between input and output as well as the efficiency, the amount of efforts that have been made yet it is still not satisfactory. In terms of efficiency, many efforts have been made but it is still not satisfactory. Observation results prove that the groups of farmers still need direction in the use of pesticides. By looking at the results of this research, it is expected in order to implement a policy, we should pay attention to the effectiveness and efficiency so that the program has been created and efforts have been conducted are able to run well and give a positive impact as well as to overcome the existing problems in the field.